Off-centered Double-slit Metamaterial for Elastic Wave Polarization Anomaly. Issue 1 (December 2017) - Lee, Hyung; Lee, Je-Ryung; Moon, Seung; Je, Tae-Jin; Jeon, Eun-chae; Kim, Kiyean; Kim, Yoon
Abstract The polarization anomaly refers to the polarization transition from longitudinal to shear modes along an equi-frequency contour of the same branch, which occurs only in some anisotropic elastic media, but the lack of natural materials exhibiting desired anisotropy makes its utilization impossible for potential novel applications. In this paper, we present a unique, non-resonant type elastic metamaterial made of off-centered, double-slit unit cells. We show that its wave polarization characteristics that determine the desired anomalous polarization for a certain application are tailorable. As an application, a mode converting wedge that transforms pure longitudinal into pure shear modes is designed by the proposed metamaterial. The physics involved in the mode conversion is investigated by simulations and experiments.